The St. Theodore Tyron Cult in the Novo Hopovo Monastery - Gugolj, Branka M. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The relics of the warrior saint Theodor Tyron were brought to the Novo Hopovo Monastery in the mid-16th century at the latest. The first records of the relics were found in a panegyric dating from 1555. Three manuscripts of the Tale of Theodore Tyron record a legend referring to the events occurring prior to the transfer of the saint's relics to Hopovo, as well as to their fate in the Fruška Gora monastery. The relics were kept in a casket and displayed in the bema, bestowing it a memorial character. Such manner of displaying the relics had already been established in the Žiča Monastery and was practised in numerous monasteries of Fruška Gora.
Keywords: cult of relics; Novo Hopovo Monastery; St Theodore Tyron